STUDY ON SERUM LACTATE DEHYDROGENASE LEVEL IN PRECANCEROUS, CANCEROUS, AND HEALTHY SUBJECTS - Sharma, Geeta; Sharma, Preeti; Kumar, Pradeep; Kumar, Randhir (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Present study was carried out to evaluate the serum level of lactate hydrogenase enzyme in normal, precancerous, and cancerous subjects independently, to probe into the possible interrelationship among them, by utilizing biochemical parameter as an adjunct or solely to diagnose the malignant condition. Methods: The study was carried out to evaluate the role of serum lactate dehydrogenase (LDH) as a biochemical parameter in the oral premalignant and malignant and normal subjects. Estimation of LDH was carried out by spectrophotometric method of Wroblewski and LaDue. Statistical analysis was done using Student's t-test. Result: An increased level of LDH was found in serum in patients with oral premalignant and malignant lesions. Moreover, the raised level of LDH had a positive correlation with the histologic grading. Conclusion: Serum LDH in normal subject is 338.82 WL unit /ml. However the mean LDH value increases to 485.66 in premalignant lesion and to 762.72 WL unit /ml in malignancy. Thus we conclude that serum LDH level increases in premalignant lesion and malignancy. Keywords: Lactate dehydrogenase, Leukoplakia, Oral cancer.